2013
DOI: 10.1258/acb.2012.012104
|View full text |Cite
|
Sign up to set email alerts
|

Association between C-reactive protein, pro-oxidant-antioxidant balance and traditional cardiovascular risk factors in an Iranian population

Abstract: This study showed that among Iranian subjects, the inflammatory marker, hs-CRP, was strongly and positively associated with a marker of oxidative stress and also with several traditional risk factors of CVD. Moreover, the impact of traditional cardiovascular risk factors on hs-CRP concentrations and PAB values differed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Not only has CRP been associated with the chain of events occurring at the endothelium within the atherosclerotic process [54, 55], but it has also been linked with a direct, independent association with future cardiovascular events in several great-scale epidemiologic reports [27, 56, 57], as well as with other disorders of metabolic origin, both in adult and pediatric populations [58, 59]. …”
Section: Cardiovascular Risk Factors: Classic Versus Novel (Table 1)mentioning
confidence: 99%
“…Not only has CRP been associated with the chain of events occurring at the endothelium within the atherosclerotic process [54, 55], but it has also been linked with a direct, independent association with future cardiovascular events in several great-scale epidemiologic reports [27, 56, 57], as well as with other disorders of metabolic origin, both in adult and pediatric populations [58, 59]. …”
Section: Cardiovascular Risk Factors: Classic Versus Novel (Table 1)mentioning
confidence: 99%
“…In addition, several inflammatory indicators [such as homocysteine, fibrinogen, white blood cell count and the C-reactive protein (CRP)] are highly correlated with the degree of OC (Zaldivar et al 2006;Darvall et al 2007;Wee et al 2008;Uysal et al 2014). Studies have shown that an elevated white blood cell count and plasma CRP levels are associated with the development of CVD (Twig et al 2012;Razavi et al 2013). However, a large body of evidence has established fibrinogen as independent risk factor for CVD, and as an important mediator through which traditional risk factors, such as low-density lipoprotein, exert their effects (Clark et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…5 ROS have been suggested as a cause of death for many cells in different pathological states including various models of liver, renal and cardiac diseases. 6 Also, clinical and experimental studies have shown that disturbing oxidant-antioxidant balance system is involved in the pathogenesis of chronic diseases such as cancer, 7 coronary heart disease, diabetes, liver injury and kidney injury. [8][9][10] Antioxidant and antioxidative enzyme activities reduce due to GM or increase of lipid peroxidation products.…”
Section: Introductionmentioning
confidence: 99%